DEKONSTRUKSI MAKNA IKLAN SABUN LUX - Wayan, Nuriarta I (Studi Budaya Nusantara, 2023)
The existence of advertising in the mass media is no longer a complementary element to the system of industrialization and capitalism, but has become the most vital instrument. This research will discuss LUX soap advertisements. LUX bath soap ads always feature beautiful women to become product icons. Because it is synonymous with exclusive advertisements and top Indonesian stars. Advertisements in LUX beauty soap products apparently have many hidden meanings. With deconstruction theory, the results show that not with the aroma and freshness of LUX soap, women will be able to actively engage in any profession, whether as young executives,artists, singers, students or activists fighting for women's rights and not with LUX soap. women will become like Maudy Ayunda, a beautiful and active woman. However, because Maudy Ayunda is an artist with many achievements, she became the star of a LUX soap commercial. In addition to her beautiful face, she also carries out various solid activities. In the process of interpreting the LUX soap advertisement, from a deconstruction point of view, there will be a reversal of meaning. The meaning is not final which shows that by using LUX soap a person will become like Maudy Ayunda, that is, appear as a beautiful and active woman. But we can convey another meaning, namely that because Maudy Ayunda is a beautiful artist, intelligent and also active, she was chosen as the star of the LUX soap advertisement.